Large decrease in paediatric hospitalisations during the COVID-19 outbreak in Japan - Yasuki Kobayashi; Atsushi Miyawaki; Masaki Nakamura; Hideki Ninomiya; Kazuaki Sano (BMJ Publishing Group, 2021)
We evaluated the nationwide trends in paediatric hospitalisations including non-emergency hospitalisations during the COVID-19 pandemic in Japan. Using inpatient data from 272 acute-care hospitals covering 12.4% of total hospitalisations of all ages, we analysed the number of hospitalisations of children (aged 1-17 years) for weeks 9-21 of 2020 (during the outbreak) versus 2017-2019. Hospitalisation decreased during the outbreak by 38.4% (adjusted incidence rate ratio, 0.60; 95% CI, 0.53 to 0.69). There were reductions in communicable diseases and trauma, possibly through non-pharmaceutical interventions, but not in appendicitis. This study highlights the potential importance of reallocating paediatric care resources during the pandemic.